Factors influencing Students' motivation to learn mathematics in Junior High School - Kartika, Nina; Yulianto, Eko; Dewi, Sinta Verawati (Jurnal Absis: Jurnal Pendidikan Matematika dan Matematika, 2024)
This study aims to identify the factors influencing students' motivation to learn mathematics at SMP Negeri 2 Kota Tasikmalaya. The research employs a quantitative approach with a factor analysis method. The study population comprises students from SMP Negeri 2 Kota Tasikmalaya, with a sample of 249 students selected using a cluster random sampling technique. Data were collected through a questionnaire designed to explore the factors affecting students' motivation to learn mathematics. Data analysis was conducted using confirmatory factor analysis (CFA), which included an analysis feasibility test, the construction of a correlation matrix, extraction process, factor rotation, and factor naming. The results indicate that students' motivation to learn mathematics is influenced by nine key factors: (1) school environment, (2) family environment, (3) talent, (4) aspirations, (5) interest, (6) perception of mathematics, (7) teacher, (8) community environment, and (9) attitude. These findings provide valuable insights for improving learning strategies in schools.